Birthright - Nora Roberts (New York Jove Books, 2004)
Overseeing the evacation of an ancient skeleton at a small-town construction site, archaeologist Callie Dunbrook copes with accidents and rumors that the project is cursed, a situation that is complicated by a stranger's claims about her past.
Keywords: Literature (3GdCOHs; General -- Fiction; Women archaeologists; Divorced women -- Fiction; Birthparents -- Fiction